Identification of mast cells in the human pericranium: possible role in the genesis of headache - Reis, Rita Santana dos; Andrade, Juliana Ramos de; Junior, Florisvaldo José Morais Vasconcelos; Valenca, Marcelo Moraes (Headache Medicine, 2023)
Full abstract in PDF.